Hydrogel-based materials as antibacterial agents and super adsorbents for the remediation of emerging pollutants: A comprehensive review - Shabnam Ahmadi; Sina Pourebrahimi; Alhadji Malloum; Majid Pirooz; Christian Osagie; Soumya Ghosh; Muhammad Nadeem Zafar; Mohammad Hadi Dehghani (Emerging Contaminants, 2024)
Hydrogels have various potential applications due to their unique characteristics and recently, hydrogels have been utilized as adsorbents in wastewater treatment because of their ability to remove contaminants from water. Constructing strong hydrogels with high adsorption capabilities is crucial for effective wastewater treatment. Scientists and researchers are working to improve the properties of hydrogels by incorporating inorganic elements into polymer networks, which further reduces the costs as well as simplifies their preparation. Natural polymers like starch and alginate are widespread due to their economic and biological advantages, such as biodegradability, biocompatibility, reduced toxicity, environmental friendliness, and low cost. The adsorption of pollutants onto hydrogels as well as their use as antimicrobial agents has garnered significant attention. This review paper summarizes the latest studies on using hydrogels as adsorbents to remove endocrine-disrupting chemicals (EDCs), persistent organic pollutants (POPs), and other emerging pollutants from water environments along with their use as antimicrobial agents. In the first step, different classes of hydrogels and different characterization techniques have been discussed. Next antimicrobial potential of hydrogels is elaborated to understand how these hydrogels can be a potential candidate for such activities. While discussing the adsorption application of hydrogels, different isothermal, kinetics and thermodynamics models have been discussed to highlight the mechanism and nature of forces involved in adsorption of pollutants. Further different simulations such as DFT and MD have been discussed to get more holistic understanding of pollutants adsorption onto hydrogels. A limited number of studies have utilized other techniques such as Monte Carlo simulations and computational fluid dynamics (CFD) so it is important to explore a variety of computational methods to gain a comprehensive understanding of the adsorption process onto hydrogels.